Preoperative Ibuprofen and Success Rate of Inferior Alveolar Block in Irreversible Pulpal Inflammation Cases - Dilawar Sultan, Mehroz Ahmad Khan, Marij Sajjad, Aiman Fayyaz, Khaqan Azam, Waqar Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The inferior dental nerve block (IDNB) is the best method of pain control prior to endodontic treatment. Conventional IDNB is one of the most common technique to get pain control Aim: To compare effectiveness of premedication with Ibuprofen with placebo to increase the success chances of IDNB in lower molars in subjects with asymptomatic irreversible pulpal infection. Methodology: Sixty patients were selected and divided in to two groups (group 1 ibuprofen and group 2 placebo). Patients were pre-medicated and the treatment was commenced with IDNB 45 minutes after premedication. The failed patients were managed with alternate methods Results: The results showed that premedication with ibuprofen gave 16.6 % success rates vs 13.3% of placebo. The mean ages in group 1 were 27.40±4.17 years and 25.73±4.79 years. The practical implication of this study is that ibuprofen can’t be used to increase the success chances of IDNB in lower molars before endodontic therapy. Conclusion: Thus it was concluded that ibuprofen as compared to placebo did not increased the success chances of IDNB in lower molars in subjects with asymptomatic irreversible pulpal infection. Key words: Ibuprofen, Irreversible pulpitis; Endodontics.